Dream sharing frequency: stability over a three-year period - Schredl, Michael; Göritz, Anja (International journal of dream research, 2020)
Cross-sectional surveys have indicated that dream sharing frequency declines with age. However, longitudinal studies are lacking in order to differentiate between possible cohort effects and changes with age. The present analysis included 867 persons (487 women, 380 men) with a mean age of 49.79 ± 13.62 years who completed two surveys in 2014 and 2017 that included scales measuring dream sharing frequency. The findings indicate that the frequency of sharing dreams did not change over a three-year period and that inter-individual differences are quite stable. This would be in line with the life-style hypothesis of Schonbar (1965) and, thus, the previously reported decline of dream sharing frequency in cross-sectional designs very likely reflect cohort effects. It would be very interesting to study whether life events like undergoing psychotherapy or having life-changing dreams affect this stable “dream-related trait”. Moreover, it would be valuable to know how this “dream-related trait” forms during childhood/adolescence.
Gesehen am 19.10.2020